The Usher syndrome proteins cadherin 23 and harmonin form a complex by means of PDZ-domain interactions - Siemens, Jan; Kazmierczak, Piotr; Reynolds, Anna; Sticker, Melanie; Littlewood-Evans, Amanda; Müller, Ulrich (Proceedings of the National Academy of Sciences of the United States of America, 2002)
Usher syndrome type 1 (USH1) patients suffer from sensorineuronal deafness, vestibular dysfunction, and visual impairment. Several genetic loci have been linked to USH1, and four of the relevant genes have been identified. They encode the unconventional myosin VIIa, the PDZ-domain protein harmonin, and the putative adhesion receptors cadherin 23 (CDH23) and protocadherin 15 (PCDH15). We show here that CDH23 and harmonin form a protein complex. Two PDZ domains in harmonin interact with two complementary binding surfaces in the CDH23 cytoplasmic domain. One of the binding surfaces is disrupted by sequences encoded by an alternatively spliced CDH23 exon that is expressed in the ear, but not the retina. In the ear, CDH23 and harmonin are expressed in the stereocilia of hair cells, and in the retina within the photoreceptor cell layer. Because CDH23-deficient mice have splayed stereocilia, our data suggest that CDH23 and harmonin are part of a transmembrane complex that connects stereocilia into a bundle. Defects in the formation of this complex are predicted to disrupt stereocilia bundles and cause deafness in USH1 patients.
Gesehen am 06.12.2021